Comparative studies of gelatinase activity in cattle and buffalo bull seminal plasma through gelatin zymography - BALAMURUGAN, T C; KRUPAKARAN, R PRAKASH; ARUNKUMAR, S; PANDIYAN, GURU D V; PERUMAL, P (The Indian Journal of Animal Sciences, 2015)
A comparative study was undertaken to study the gelatinase activity in seminal plasma of Murrah buffalo and Jersey crossbred cattle bull through gelatin zymography. In gelatin zymography, the presence of 3 prominent bands at 220 KDa, 92 KDa and 72 KDa for both buffalo and cattle seminal plasma were observed. All these 3 forms are proteolytically active, degraded the gelatin in gelatin zymography. The 220 KDa homodimer of MMP-9 was very prominent in buffaloes semen compared to cattle semen. On the contrary, 135 KDa heterodimer of MMP -9 was observed only in cattle seminal plasma. The 72 KDa band was very feeble in both the cases. The level of expression of 220 KDa and 92 KDa bands was constant compared to that of 72 KDa. The relative amount of 92 KDa band to that of 72 KDa band was at least 3-5 times higher. The difference between buffalo and cattle seminal plasma was very obvious by the presence of 135 KDa band. On gelatin zymography, the distinguished feature of cattle seminal plasma was the presence of 135 KDa heterodimer of MMP. It is concluded that the 135 KDa band was observedonly in cattle seminal plasma. Further, more upregulation of MMP-9 mediated through MMP-2 activity was observed in buffalo seminal plasma.